ANALISIS PENGARUH STRES KERJA, BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN PADA YAYASAN PENDIDIKAN BHAKTI SUCI PURWODADI KABUPATEN GROBOGAN - Egiliana Atika Putri; Sarbullah Sarbullah (Sekolah Tinggi Ilmu Ekonomi Semarang, 2022)
the purpose of this study was to determine the effect of work stress, workload, and work environment on employee turnover intention at the Bhakti Suci Education Foundation. High employee turnover rates result in organizations becoming ineffective, losing experienced employees and needing to train new employees. high work stress and a good work environment will affect the decrease in the level of turnover intention, while a high workload will affect the increase in turnover intention. The population in this study were all employees of the Bhakti Suci Purwodadi Education Foundation, Grobogan Regency, with a sample of 60 respondents. The sampling technique in this study was a saturated sample or census sample, where all members of the population were sampled. Results of data analysis For the classical assumption test as a whole the data is normally distributed. The results of the t-test in this study indicate that the work stress variable (X1) has a partial effect on turnover intention with a significant value of 0.742, workload variable (X2) has a partial or separate effect on employee turnover intention with a significant value of 0.00. Work environment variable (X3) has a partial or separate effect on employee turnover intention with a significant value of 0.035.